PRECIOUS DESCRIPTION OF TRADEMARKS, CORRELATION INDICATORS BETWEEN TRADEMARKS AND RELATIONSHIPS BETWEEN VALUABLE TRADEMARKS (International journal of artificial intelligence, 2025)
This article analyzes the morphological and physiological characteristics of valuable agronomic traits in cotton ( Gossypium barbadense L. ), such as yield, fiber output, fiber length, strength, and earliness, as well as the correlation relationships among these traits. The study revealed medium to strong positive correlations between fiber quality indicators and yield, while fiber length and lint percentage showed a negative relationship with the duration of the vegetative period. The obtained results provide a scientific basis for the complex evaluation of valuable traits and for improving the efficiency of breeding selection in fine-fiber cotton .